2021
DOI: 10.1109/tap.2021.3060581
|View full text |Cite
|
Sign up to set email alerts
|

Radar Cross Section Pattern Measurements in a Mode-Stirred Reverberation Chamber: Theory and Experiments

Abstract: This paper deals with the ability to perform radar cross-section (RCS) pattern measurements within reverberation chambers (RCs). The characterization principle is based on the estimation of the back-scattered field from the target at a farfield distance and takes advantage of the diffuse field within the RC. A frequency sweep of scattering parameters is achieved in presence and absence of the target installed on a rotating mast and the pattern is retrieved from these measurements. This paper explains the under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 17 publications
(20 reference statements)
0
20
0
Order By: Relevance
“…where ⟨•⟩ α is an ensemble average performed over the stirrer positions α which allows reducing the noise [14], [12]. We can notice that ℜ (∆ S (f, θ, Γ L1 , Γ L2 )) behaves as a sine signal as a function of frequency with a c/2R period.…”
Section: Measurement Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…where ⟨•⟩ α is an ensemble average performed over the stirrer positions α which allows reducing the noise [14], [12]. We can notice that ℜ (∆ S (f, θ, Γ L1 , Γ L2 )) behaves as a sine signal as a function of frequency with a c/2R period.…”
Section: Measurement Methodsmentioning
confidence: 99%
“…However, it has been shown that RCs can also be used to retrieve line-of-sight parameters [10], [11]. In particular, based on an original radar cross-section (RCS) measurement method [12], a contactless method to retrieve the antenna gain pattern within RCs has been introduced in 2021 [13]. This method relies on a sinusoidal regression process applied on an S-parameter difference for two different AUT load conditions.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, an average of ( 7) is performed over a stirrer rotation. Besides, to compensate the variation over the frequency range of the measurement antenna properties along with the wavelength and the load reflection coefficients that impacts the sine wave amplitude according to (2) and ( 7), the term σ max r (f, θ) is extracted using a regression process from the corrected difference ∆ S in (8) (see [10] for full details).…”
Section: B Antenna Gain Extractionmentioning
confidence: 99%
“…The Fig. 3 presents |Γ L | for the OC and 50 Ω loads computed using (10). The OC case exhibits losses of about 1.5 dB on average over the frequency band; these are mainly due to the switch insertion losses.…”
Section: A Experimentsmentioning
confidence: 99%
“…For this reason, RCS values are commonly obtained through measurement [3], [4]. RCS measurement is well-documented for a single frequency, but measuring RCS over a wide bandwidth presents additional challenges [5]- [7]. Rather than building a new measurement system to measure RCS at a single frequency, this work aims to apply measurement theory to an existing W-band system to extract RCS without purchasing additional hardware.…”
Section: Introductionmentioning
confidence: 99%